NUCLEAR DENSITIES AND THE STATISTICS OF NUCLEONIC CONSTITUENTS - Betz, M.; Hadjimichef, D. (American Physical Soc, 1994)
In the quark model of the nucleon, the Fermi statistics of the elementary constituents can influence significantly the properties of multinucleon bound systems. In the Skyrme model, on the other hand, the basic quanta are bosons, so that qualitatively different statistics effects can be expected a priori. In order to illustrate this point, we construct schematic one-dimensional quark and soliton models which yield fermionic nucleons with identical baryon densities. We then compare the baryon densities of a two-nucleon bound state in both models. Whereas in the quark model the Pauli principle for quarks leads to a depletion of the density in the central region of the nucleus, the soliton model predicts a slight increase of the density in that region, due to the bosonic statistics of the meson-field quanta.